2013
DOI: 10.1186/1471-2334-13-507
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis to compare the accuracy of GeneXpert, MODS and the WHO 2007 algorithm for diagnosis of smear-negative pulmonary tuberculosis

Abstract: BackgroundSmear-negative pulmonary tuberculosis (SN-PTB), which is common in HIV-infected patients, is difficult to diagnose using smear microscopy alone. In 2007, the WHO developed an algorithm to improve the diagnosis and management of smear-negative tuberculosis in HIV prevalent and resource constrained settings. Implementation of the algorithm required individuals with presumptive TB to be initially evaluated using two sputum microscopy examinations followed by clinical diagnosis that may include chest X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 39 publications
5
82
1
3
Order By: Relevance
“…Recently Walusimbi et al (14) reviewed its diagnostic performance and reported that its pooled sensitivity for smear-negative, culture-positive cases, based on 15 different reports, was 67z, and that the specificity was 98z, which are again comparable to the LAMP-TB test results of this study.…”
Section: Discussionsupporting
confidence: 75%
“…Recently Walusimbi et al (14) reviewed its diagnostic performance and reported that its pooled sensitivity for smear-negative, culture-positive cases, based on 15 different reports, was 67z, and that the specificity was 98z, which are again comparable to the LAMP-TB test results of this study.…”
Section: Discussionsupporting
confidence: 75%
“…Latest generation liquid culture diagnostics and molecular line probe assays are costly and cannot be performed in resource-limited settings, due to need for biosafety measures and specialised staff [4]. Besides technical expertise and biosafety concerns, LowensteinJensen (LJ) method, "the gold standard test", takes several weeks to produce result causing delayed onset of treatment [6]. In December 2010, WHO recommended use of a new Cartridge Based Nucleic Acid Amplification test (CB-NAAT), named GeneXpert system [1].…”
Section: Introductionmentioning
confidence: 99%
“…Prompt and accurate TB diagnosis are prerequisite for early and effective treatment thereby reducing tuberculosis burden, but there are number of difficulties in achieving the goal. Sputum smear microscopy is inefficient due to its variable sensitivity particularly in patients with sputum smearnegative and/or extrapulmonary disease, and drug-resistant TB [4][5][6]. Latest generation liquid culture diagnostics and molecular line probe assays are costly and cannot be performed in resource-limited settings, due to need for biosafety measures and specialised staff [4].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, further guidelines are needed to address these gaps in diagnosis for GeneXpert negative and sputum scarce patients. 25 …”
Section: Gaps In Diagnosismentioning
confidence: 99%
“…25 In high HIV-TB burden environments, empiric treatment is often used to offset the diagnostic limitations and provide, possibly, same day treatment to decompensating patients. [21][22][23][24][25] The few studies presenting diagnostic information on GeneXpert negative individuals suggest that smear microscopy and chest x-ray have limited utility in detecting culture positive, Xpert negative, extrapulmonary or disseminated TB. 6,11 For sputum scarce patients, rapid diagnostics using other samples such as urine (urine LAM or urine GeneXpert) or blood may prove more feasible for testing.…”
Section: Gaps In Diagnosismentioning
confidence: 99%